North Aceh Regional Innovation Policy in the face of reduced Regional Fiscal Capacity after the end operational PT. Arun. LNG - Ferizaldi, Ferizaldi; Hasyem, Muhammad (LPPM Universitas Malikussaleh, 2021)
Through Law no. 11 of 2006 concerning the Government of Aceh. Aceh has very broad powers, especially in the area of fiscal decentralization, which allows the Aceh government to have greater discretion in maximizing its fiscal needs. The phenomenon that occurred in North Aceh is very paradoxical with the fact that the North Aceh Government experienced a very large budget deficit after the end of PT. Arun. LNG as a contributor to oil and gas revenue sharing. This study aims to find out what innovation policies are carried out by the North Aceh Regency Government to overcome the budget deficit after the end of PT. Arun LNG. The results of the study show that various policies have been carried out by the North Aceh government but are still short-term in nature. So it can be concluded that the North Aceh Government does not have Social Accountability in implementing Aceh's Special Autonomy. In the Medium-Term Development Plan, a major policy that is substituted for income that will be lost after the end of the operations of PT. Arun.LNG so that the budget deficit can be overcome and the regional fiscal gap does not become negative.Through Law no. 11 of 2006 concerning the Government of Aceh. Aceh has very broad powers, especially in the area of fiscal decentralization, which allows the Aceh government to have greater discretion in maximizing its fiscal needs. The phenomenon that occurred in North Aceh is very paradoxical with the fact that the North Aceh Government experienced a very large budget deficit after the end of PT. Arun. LNG as a contributor to oil and gas revenue sharing. This study aims to find out what innovation policies are carried out by the North Aceh Regency Government to overcome the budget deficit after the end of PT. Arun LNG. The results of the study show that various policies have been carried out by the North Aceh government but are still short-term in nature. So it can be concluded that the North Aceh Government does not have Social Accountability in implementing Aceh's Special Autonomy. In the Medium-Term Development Plan, a major policy that is substituted for income that will be lost after the end of the operations of PT. Arun.LNG so that the budget deficit can be overcome and the regional fiscal gap does not become negative.